Gelatine based films added with bacteriocins and a flavonoid ester active against food-borne pathogens - Ibarguren, Carolina (2015)
Active films, based on food grade gelatine added with bacteriocins and/or the flavonoid ester prunin laurate as antimicrobial compounds, were prepared. The films were characterized by water vapor permeability, mechanical property measurements and scanning electron microscopy. Film antibacterial activity was determined by the agar diffusion and direct contact microplate techniques against Listeria monocytogenes 01/155, Staphylococcus aureus ATCC29213 and Bacillus cereus 1. Physical properties of gelatine films were not significantly affected by active compound incorporation. Antibacterial effect on each strain was dependent on the active compound incorporated into the film, but in all cases a synergistic inhibitory action was observed when both antimicrobial compounds were added. Thus, the results of this study suggest that gelatine based active films here presented could provide an alternative strategy for food biopreservation. Industrial relevance This work proposes the elaboration of active films based on food grade gelatine and the addition of enterocins A, B and P synthesized by Enterococcus faecium SM21 and the flavonoid ester, prunin laurate, as antimicrobial active compounds. Films were prepared using a simple and low cost methodology and their application can be adapted to different kinds of food systems. The inclusion of the antimicrobial compounds on the film matrix did not alter their functional properties. The obtained films were active against L. monocytogenes, S. aureus and B. cereus, providing an alternative tool for food preservation, especially in the case of foods susceptible to contamination by these pathogens. Although the inhibitory effect of active films was different for each indicator strain, in all cases a synergistic inhibition effect was observed when both active compounds, ES and PL, were added to gelatine films. This synergistic effect between both antimicrobial compounds offers a novel potential hurdle technology for food preservation.